Evaluation of WC-10Ni thermal spraying coating by HVOF on the fatigue and corrosion AISI 4340 steel - Voorwald, Herman Jacobus Cornelis [UNESP]; Vieira, L. F. S. [UNESP]; Cioffi, M. O. H. [UNESP] (Elsevier B.V., 2010)
Shot peening is a surface process widely used to improve the fatigue strength of materials, through compressive residual stresses induced in their surface layers. Considering mechanical components for high responsible applications, wear and corrosion control is currently accomplished by the use of coated materials.In the case of chrome plating or hard anodizing, lower fatigue strength in comparison to uncoated parts are associated to high residual tensile stresses and microcracks density. Under constant or variable amplitude loading microcracks will propagate and cross the interface coating substrate without impediment.The aim of the present study is to analyze the influence of WC-10Ni coating applied by HVOF process on the axial fatigue strength of AISI 4340 steel. The shot peening effect on the fatigue performance of coated AISI 4340 steel was also evaluated. The fractured fatigue specimens were investigated using a scanning electron microscope in order to obtain information about the crack initiation points. (C) 2010 Published by Elsevier Ltd.
Keywords: Shot peening; Residual stress; 4340 Steel; Fatigue; HVOF process